A new species of the Indonemoura fujianensis complex (Plecoptera: Nemouridae) from the Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2020)
A new species of Nemouridae of the genus Indonemoura Baumann, Indonemoura maoershana sp. nov., is described from Maoershan National Natural Reserve in the Guangxi Zhuang Autonomous Region of southern China, and is recognized as member of the I. fujianensis complex. This new taxon is compared with similar congeners.